1998
DOI: 10.1046/j.1365-2125.1998.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin population pharmacokinetics in children and adults with uncomplicated falciparum malaria

Abstract: Aims To investigate the pharmacokinetics of the antimalarial artemisinin in the field setting using sparsely collected data. Methods Artemisinin concentrations were determined by h.p.l.c. in a total of 107 capillary plasma samples collected on the first day and in 33 samples on the last day of a 5-day oral artemisinin regimen of 10 mg kg −1 day −1 in 23 paediatric (aged 2-12 years) and 31 adult (aged 16-45 years) Vietnamese patients with uncomplicated falciparum malaria. The population model was developed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 2 publications
1
11
1
Order By: Relevance
“…The increase is in accordance with earlier findings based on concentrations in plasma in both malaria patients and healthy volunteers (1,(3)(4)(5). The extent of the increase in artemisinin CL s /F values has been reported to be six-to sevenfold after standard treatment (1,4,22). In our study, the average increase in CL s /F from day 1 to 5 in the patients in the standarddose group was 5-fold, whereas the average increase in the escalating-dose group was 2.5-fold.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The increase is in accordance with earlier findings based on concentrations in plasma in both malaria patients and healthy volunteers (1,(3)(4)(5). The extent of the increase in artemisinin CL s /F values has been reported to be six-to sevenfold after standard treatment (1,4,22). In our study, the average increase in CL s /F from day 1 to 5 in the patients in the standarddose group was 5-fold, whereas the average increase in the escalating-dose group was 2.5-fold.…”
Section: Discussionmentioning
confidence: 45%
“…In a population kinetic study, lower CL/F values and volumes of distribution for artemisinin were found in female children (22). However, due to the small number of male and female children involved, sex was not concluded to influence the pediatric artemisinin kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…And the results of various clinical trials suggest that artemisinin derivatives are relatively safe drugs. 33,34) Our results clearly show for the first time that artemisinin and its derivatives are very potent compounds that can be used in combination with anticancer drugs to overcome MDR phenomena. …”
Section: Co-treatment Using Pirarubicin and Qinghaosu Or Doxorubicin mentioning
confidence: 90%
“…25,26 Despite the relative lack of resistance to artemisinin derivatives noted to date, the cure rates using these drugs may be affected by the observed inter-individual variability in drug pharmacokinetics. 27 While there are several reasons for this variability, absorption from an intramuscular injection site may be unpredictable, especially in children who are comatose with little muscle activity. Two of the artemotil deaths in our study had parasitemia at the time of death, one at 38 hours and the other at 140 hours after the start of therapy.…”
Section: Discussionmentioning
confidence: 99%